REQUIREMENTS FOR COLD-WEATHER RESEARCH - Fletcher,J. O. (1967)
Since World War II the Air Force's generation of requirements for cold-weather research and development has been very effective in removing cold-weather limitations on equipment and on normal methods of operation. However, the Air Force has largely failed to generate requirements for new methods of operation that would exploit unique environmental factors in cold regions. (Author) Presented at the Air Force/Industry Conference (57th), Mission Inn, Riverside, California, March 8, 1967.